Image analysis, methanogenic activity and molecular biological techniques to monitor granular sludge from an egsb reactor fed with oleic acid - Pereira, M. A. (2003)
Morphological changes in anaerobic granular sludge fed with increasing loads of oleic acid were quantified by image analysis. The combination of this technique with data on the accumulation of adsorbed long chain fatty acid give insight into the mechanisms of sludge disintegration, flotation and washout The molecular characterization of microbial community indicated that the bacterial domain was affected during sludge disintegration, flotation and washout. The archaeal domain was less affected although no acetoclastic and only a residual hydrogenotrophic activity were detected at the end of the operation.